Country Benchmarking for Setting Up a New Business - Avram, Bianca; Brad, Stelian (Development, Growth and Finance of Organizations from an Eastern European Context, 2017)
The analysis of the form in which a business is founded is highly important for the economic development of a country and the regulation of the administrative sector can improve economic performances. This paper is intended to address the study of the manner in which the social and economic development indicators affect the number of procedures and time required to start a business and also the financial aspect that characterizes this entrepreneurial activity. In order to carry out this analysis, we have constructed a sample, which includes 125 countries pertaining to all continents for which we have recorded, besides the three variables, the values for the social and economic development indicators. We have completed our analysis through the graphical representations of the variables that define the administrative framework as a function of the social progress index, respectively, GDP/capita. Consequently, after constructing these graphs and computing the correlation coefficient, we have discovered reverse connections between all combinations of the variables that are subject to our study. The results obtained have implications in the development of the business sector and aid the legal mechanisms to implement regulations and norms aimed to facilitate the access of future entrepreneurs to the business environment.